Predictors of Severity in Childhood Pancreatitis: Correlation With Nutritional Status and Racial Demographics. Issue 3 (April 2015) - Vasilescu, Alexandra; Cuffari, Carmen; Santo Domingo, Lisa; Scheimann, Ann O.
Abstract : Objective: Acute pancreatitis is one of the leading causes of rising pediatric hospitalizations in North America. The aim of this study was to assess the role of nutritional status and racial influences on the severity of acute pancreatitis in children. Methods: The institutional review board approved this retrospective chart review of children with the diagnosis of acute pancreatitis between the ages of 0 and 18 years hospitalized at the Johns Hopkins Hospital between 1998 and 2008. Parameters studied included biochemical markers associated with pancreatitis, review of severity of illness reflected through the length of stay, and pediatric intensive care unit admission. Results: The length of in-patient hospitalization was longer for children with imaging findings of pseudocyst or pancreatic necrosis (23.1 ± 26.4 days vs 4.4 ± 10.6 days; P = 0.0074) and malnourished children versus normal weight and obese children (16.5 days for malnourished vs 10.6 days for normal weight vs 10.7 days for obese; P = 0.04). There was also a significant difference in the need for pediatric intensive care unit admission across ethnic groups (18% African American vs 7% white) ( P = 0.04). Conclusions: Ethnicity and nutritional status may influence the severity and duration of hospitalization among children with pancreatitis.